Voluntary markets for carbon offsets: evolution and lessons for the LNG market - Bose, A; Cohen, J; Fattouh, B; Johnson, O; Spilker, G (Oxford Institute for Energy Studies, 2021)
National commitments to cut greenhouse gas (GHG) emissions currently fall far short of what is needed to meet the goal of the 2015 Paris Agreement to limit global warming to 1.50 C and no more than 20 C. Meeting this goal will require an estimated 45% reduction in global emissions by 2030, reaching net-zero emissions by 2050 with a continuing decline beyond that date. In response to this imperative, companies in every economic sector, along with national and regional governments, cities, universities, and investors are making their own commitments to reach net-zero emissions.